Minor sanctions before inadmissible strikes. Analysis of Supreme´s Court jurisprudential doctrine - Trelles Garrido Lecca, Carlos Arturo (2023)
This paper analyzes the mandatory jurisprudential doctrine issued by the Second Constitutional and Social Transitory Chamber of the Supreme Court of the Republic of Peru, regarding the possibility of imposing minor sanctions to workers who execute a strike that has been declared inadmissible. For this purpose, the characteristics of the right to strike according to the Political Constitution of Peru of 1993 and the harmonizing theory of fundamental rights have been taken into account.